Saṃskṛta vāṅmaya meṃ purūṣa: eka paricayātmaka kośa; Rāmāyaṇa, Mahābhārata evaṃ Purāṇoṃ ke viśeṣa sandarbha meṃ = Sanskrit vāṅmaya : meṅ puruṣa eka paricayātmaka kośa, with special reference to Rāmāyaṇa, Mahābhārata and Purāṇas - Bainarjī, Siprā (Pārimala Saṃskr̥ta granthamālā 106, 2009)
Dictionary of male characters in Sanskrit literature; with special reference to Rāmāyaṇa, Mahābhārata and Puranas, Hindu sacred books